(untitled) (Journal of Enam Medical College, 2017)
Background: The position and size of isthmus of thyroid gland varies considerably in human with age, sex, physiologic state, race and geographical location and sometimes the isthmus may be absent. So this study was designed to find out the macroscopic differences in isthmus of thyroid gland of different age and sex groups in Bangladeshi people. Objective: To record the macroscopic characteristics of isthmus of thyroid gland with advancing age in both sexes with a view to help establishing normal standard of Bangladeshi people. Materials and Methods: This descriptive cross-sectional study was carried out on 54 autopsied human thyroid glands aged 5 to 65 years. Thyroid glands were collected from unclaimed dead bodies autopsied in the morgue of Sylhet M. A. G. Osmani Medical College, Sylhet. The collected specimens were divided into groups A (20 years and below), B (21 to 50 years) and C (50 years and above). All specimens were examined morphologically by careful gross dissection method. Results: The isthmus was absent in 5.56% cases. In most of the cases (35.29%) it was against the 1st4th tracheal rings. There was significant difference in length between Group A and Group C (p<0.05) and in breadth between Group A and Group C and between Group B and Group C (p<0.05). No significant difference was found in length, breadth and thickness of isthmus of the thyroid gland between males and females. Conclusion: The presence or absence, positional change and variation in gross dimension of isthmus of thyroid gland were evident in human. The macroscopic difference was found with increasing age but not with sex. J Enam Med Col 2017; 7(1): 15-19